2021
DOI: 10.1101/2021.01.22.21249812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude and timing of the antiviral response determine SARS-CoV-2 replication early in infection

Abstract: The interferon response is a potent antiviral defense mechanism, but its effectiveness depends on its timing relative to viral replication. Here, we report viral replication and host response kinetics in patients at the start of SARS-CoV-2 infection and explore the impact of these kinetics experimentally. In both longitudinal patient nasopharyngeal samples and airway epithelial organoids, we found that SARS-CoV-2 initially replicated exponentially with a doubling time of ∼6hr, and induced interferon stimulated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Using a similar experimental design, our preliminary in vitro infection model suggested that prior RV-A16 infection could suppress SARS-CoV-2 replication using HBEC (Supplementary Figure 4). A recent finding suggested that the protective effect conferred by prior EV exposure in respiratory cells is again due to the induction on IFN-stimulated genes shared high consistency with our findings 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Using a similar experimental design, our preliminary in vitro infection model suggested that prior RV-A16 infection could suppress SARS-CoV-2 replication using HBEC (Supplementary Figure 4). A recent finding suggested that the protective effect conferred by prior EV exposure in respiratory cells is again due to the induction on IFN-stimulated genes shared high consistency with our findings 26 .…”
Section: Discussionsupporting
confidence: 92%
“…The interplay between IFNs and COVID-19 disease progression is complex, and despite initial findings, there is currently no clear evidence for a genetic immune predisposition to severe COVID-19 (Meisel et al, 2021;Povysil et al, 2021). Nevertheless, there is evidence at early iScience Article stages of infection that SARS-CoV-2 is sensitive to ISG induction and IFNs are being discussed as a treatment option (Cheemarla et al, 2021;Hasselbalch et al, 2021;Yang et al, 2021). In this light, our findings could inform future therapeutic approaches.…”
Section: Discussionmentioning
confidence: 77%
“…Type I IFNs (IFN-α and IFN-β) and type III IFNs (IFN-λ) provide potent antiviral immunity against SARS-CoV-2 via ISG protein expression [30][31][32] . However, SARS-CoV-2 replication is more rapid than the antiviral IFN responses at a higher viral load 33 . Under these conditions, the IFN responses cannot limit viral replication and may induce inflammatory responses, thereby causing tissue damage 31 .…”
Section: Discussionmentioning
confidence: 99%